A robust and rapid liquid chromatography tandem mass spectrometric method for the quantitative analysis of 5‐azacytidine. (17th August 2015) - Anders, Nicole M.; Wanjiku, Teresia M.; He, Ping; Azad, Nilofer S.; Rudek, Michelle A.
Abstract: The DNA methyltransferase inhibitor 5‐azacytidine is being evaluated clinically as an oral formulation to treat various solid tumors. A sensitive, reliable method was developed to quantitate 5‐azacytidine using LC‐MS/MS to perform detailed pharmacokinetic studies. The drug of interest was extracted from plasma using Oasis MCX ion exchange solid‐phase extraction 96‐well plates. Chromatographic separation was achieved with a YMC J'sphere M80 C18 column and isocratic elution with a methanol–water–formic acid (15:85:0.1, v/v/v) mobile phase over a 7 min total analytical run time. An AB Sciex 5500 triple quadrupole mass spectrometer operated in positive electrospray ionization mode was used for the detection of 5‐azacytidine. The assay range was 5–500 ng/mL and proved to be accurate (97.8–109.1%) and precise (CV ≤ 9.8%). Tetrahydrouridine was used to stabilize 5‐azacytidine in blood/plasma samples. With the addition of tetrahydrouridine, long‐term frozen plasma stability for 5‐azacytidine at −70°C has been determined for at least 323 days. The method was applied for the measurement of total plasma concentrations of 5‐azacytidine in a cancer patient receiving a 300 mg oral daily dose. Copyright © 2015 John Wiley & Sons, Ltd.